Induction of spermatogenesis in hypogonadotrophic hypogonadism. Issue 636 (October 1978) - Spitz, I. M.; Schumert, Z.; Steiner, J.; Rosen, E.; Segal, S.; Slonim, A.; Rabinowitz, D.
Abstract : A young male who presented with isolated bihormonal gonadotrophin deficiency is described, Basal levels of LH and FSH were low and there was no response to clomiphene citrate or LHRH. The remaining anterior pituitary function was intact. The administration of a combination of human menopausal gonadotrophin and human chorionic gonadotrophin caused testicular maturation with spermatogenesis and full androgenization. The patient was able to father a child.